Specific K-ras2 Mutations in Human Sporadic Colorectal Adenomas Are Associated with DNA Near-Diploid Aneuploidy and Inhibition of Proliferation - Giaretti, Walter (American Society for Investigative Pathology, 1998)
Recent studies indicate that p21ras proteins mediate their multiple cell functions through interactions with multiple effectors and that the number of new effectors is growing. We recently reported that K-ras2 mutations in human colorectal adenomas were associated with chromosome instability and proliferation changes. In the present study, we extend these previous observations. Hereditary and multiple (n ≥ 5) adenomas and adenomas with early cancer were excluded. Dysplasia was moderate in 91 cases and high in 25, and the median adenoma size was 1.5 cm. K-ras2 spectrum analysis was done by sequence-specific oligonucleotide hybridization using nuclear suspensions provided by analysis and sorting of multiparameter flow cytometry. In particular, tissue inflammatory cells were separated for DNA diploid tumors, whereas DNA aneuploid epithelial subclones were analyzed separately. K-ras2 mutations and DNA aneuploidy were both detected in 29 of 116 (25%) cases. DNA aneuploid index was in the near-diploid region in the majority of cases. DNA aneuploidy was strongly associated with G→C/T transversions. An association was also found between low S-phase values and G→A transitions. These findings were confirmed using multivariate logistic regression analysis to account for the effects of size, dysplasia, site, type, age, and sex. These data suggest that specific K-ras2 mutations in a subgroup of human sporadic colorectal adenomas play a role in chromosome instability and, contrary to expectations, are associated with inhibition of proliferation.